Warthin-Like Papillary Thyroid Carcinoma Associated with Lymphadenopathy and Hashimoto’s Thyroiditis - Karla Judith González-Colunga; Abelardo Loya-Solis; Luis Ángel Ceceñas-Falcón; Oralia Barboza-Quintana; René Rodríguez-Gutiérrez (Case Reports in Endocrinology)
Defining the histologic variant of thyroid carcinoma is an important clinical implication as their progression, recurrence, aggressiveness, and prognosis differ. Warthin-like variant is one of the rarest histologic variants of papillary thyroid cancer. A 36-year-old female sought consult for assessment of a painless right neck tumor. High-resolution neck ultrasound revealed a right hypoechoic, 1.71 × 1.05 cm thyroid nodule. Ultrasound-guided fine-needle aspiration biopsy report was a Bethesda grade III. Thyroid function tests showed Hashimoto’s thyroiditis. The patient underwent right hemithyroidectomy. Microscopically, the tumor was composed of papillae lined by cells with eosinophilic cytoplasm, nuclear chromatin clearing, grooves, and pseudoinclusions and a characteristic lymphoplasmacytic infiltrate of the papillae cores. Extension into the perithyroidal soft tissue and 3 ipsilateral lymph nodes was found to be positive for cancer. Warthin-like variant is an uncommon and relatively unknown variant of papillary thyroid carcinoma that has been usually associated with an excellent prognosis. Interestingly, BRAF mutations have been reported to be present in up to 75% of the patients. It is frequently associated with Hashimoto’s thyroiditis and presents unique morphological features that make it recognizable on histologic examination. The cytological diagnosis is difficult to assess due to the overlap in its findings with the classical variant and Hashimoto’s thyroiditis.